2022
DOI: 10.1088/1361-6528/ac6817
|View full text |Cite
|
Sign up to set email alerts
|

Self-powered, low-noise and high-speed nanolayered MoSe2/p-GaN heterojunction photodetector from ultraviolet to near-infrared wavelengths

Abstract: Integration of nanolayered metal chalcogenides with wide-bandgap semiconductors forming pn heterojunction leads to the way of high-performance photodetection. This work demonstrates the fabrication of a few nanometer thick Molybdenum diselenide (MoSe2)/ Mg-doped Gallium Nitride (p-GaN) heterostructure for light detection purposes. The device exhibits low noise broadband spectral response from ultraviolet to near-infrared range (300 nm – 950 nm). The band-alignment and the charge transfer at the MoSe2/p-GaN int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Furthermore, as illustrated in Figure 5f,g, the fully vertical p‐Mo x Re 1‐ x S 2 /GaN photodetector showcases the most superior performance when exposed to 365 nm light irradiation. From similar devices in the benchmark, [ 21,25,71–97 ] it exhibits an impressively low NEP value of 7.26 × 10 −18 W/Hz 1/2 , indicating excellent sensitivity, and achieves the highest D * value of 6.13 × 10 14 Jones, reflecting its outstanding detectivity. The superiority of vertical devices over others primarily lies in the fact that, compared to lateral devices, the current flows longitudinally in vertical devices, allowing for a larger conduction area capable of withstanding higher power densities.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as illustrated in Figure 5f,g, the fully vertical p‐Mo x Re 1‐ x S 2 /GaN photodetector showcases the most superior performance when exposed to 365 nm light irradiation. From similar devices in the benchmark, [ 21,25,71–97 ] it exhibits an impressively low NEP value of 7.26 × 10 −18 W/Hz 1/2 , indicating excellent sensitivity, and achieves the highest D * value of 6.13 × 10 14 Jones, reflecting its outstanding detectivity. The superiority of vertical devices over others primarily lies in the fact that, compared to lateral devices, the current flows longitudinally in vertical devices, allowing for a larger conduction area capable of withstanding higher power densities.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant change in photocurrent observed under negative bias. The theory of thermionic emission [40,41] of charge carriers can be used to interpret the asymmetric behaviour of current at negative and positive biased potentials in the I-V curve. This suggests that the current passage in the heterojunction is guided by the recombination and tunnelling mechanisms, instead of only the transport of carriers by thermionic emission.…”
Section: Photodetector Measurementsmentioning
confidence: 99%
“…Clerjaud et al [11] investigated the infrared spectra of the local vibrational modes of Mg-H in GaN under polarized light by organometallic vapor phase epitaxial growth method and found that the vibrational modes of the complexes aligned along the c-axis could not be observed based on optical configuration. Sandhu et al [12] designed MoSe 2 /p-GaN heterojunction photodetection and found low noise response to a broadband spectral from UV to NIR near-infrared (IR) range (300-950 nm). Liu et al [13] investigated the Bragg reflection distribution of porous GaN NIR by using an electrochemical oxidation method and found that the peak reflectance of the reflector was approximately 95% in the range of 550-1750 nm.…”
Section: Introductionmentioning
confidence: 99%